(untitled) (Research, Society and Development, 2021)
The objective is to show the variability of meteorological elements in the hydrographic basin area of the hydrographic basin of the Uruçuí Preto River–PI/Brazil, aiming to contribute to sustainable development in the productive areas of agriculture, laser, and hydrology. The meteorological elements studied are air temperature and relative humidity and their fluctuations, thermal amplitude, wind (intensity and direction), total insolation, cloud cover, evaporation, evapotranspiration, and rainfall. The data were from the 1960-1990 series, acquired by the Superintendency of the Development of the Northeast and by the Technical Assistance and Rural Extension Company of Piauí. The maximum annual temperature is 32.1°C, its minimum 20.0°C, with an average annual temperature of 26.1°C. A climatic classification was used according to the KÖPPEN systems, where two climatic types are distinguished in the Uruçuí Preto/PI river basin, the Aw, tropical hot and humid, with rain in summer and dry in winter; Bsh, warm semi-arid, with summer rains and dry winter. The variation of the thermal amplitude is from 11.9 to 14.9ºC. The average relative humidity of the air was 47 to 79%; the average annual precipitation was 937.7 mm; it was observed that the annual march of relative humidity follows the annual distribution of precipitation because the precipitation was the feeding process from natural sources of water vapor and moisture. Total Sunstroke in the BHRUP area ranges from 2520 to 2750 hours. It is concluded that the maximum annual temperatures increased during the period, which can cause several socioeconomic problems, and human health.